Interrupted transit and common mental disorders among migrants in Tijuana, Mexico. (August 2022) - Bojorquez, Ietza; Sepúlveda, Jaime; Lee, Deandra; Strathdee, Steffanie
Background: Policies of migration contention can interrupt the transit of people on the move, forcing them to remain in wait in non-destination countries. This liminal condition might impact negatively on migrants' mental health. Aims: To assess the relationship between interrupted transit and common mental disorders (CMD; symptoms of depression or anxiety), among migrants in shelters in Tijuana, Mexico. Methods: Cross-sectional survey conducted in November to December 2020 and February to April 2021. We assessed depressive symptoms with the Centers for Epidemiological Studies Depression scale (CES-D-7), and symptoms of anxiety with the Generalized Anxiety Disorder scale (GAD-2). We evaluated the association of being in interrupted transit (sent back from the United States to Mexico), as compared to having not crossed to the United States yet or planning to stay in Mexico, with having a CMD (either depressive or anxiety symptoms), as well as the association of other migration-related variables with CMD. Results: Being in interrupted transit (OR = 1.74, 95% CI [1.12, 2.71]), and having experienced violence during transit (OR = 2.50, 95% CI [1.63, 3.82]) were associated with CMD. Conclusions: Interrupted transit is a potential risk factor for mental health problems among migrants. Migration and public health policies should consider the mental health consequences of interrupted transit, and promote initiatives to address the mental health needs of migrants on the move.